Retroviruses of the Human Virobiota: The Recycling of Viral Genes and the Resulting Advantages for Human Hosts During Evolution - Luganini, Anna; Gribaudo, Giorgio (Frontiers in Microbiology, 2020)
All humans are colonized by a vast diversity of microbes (bacteria, archaea, protozoa, yeast and fungi; collectively referred to as the microbiota) and viruses (the virobiota). This latter group includes viruses infecting prokaryotic cells (bacteriophages), viruses infecting eukaryotic-host cells, and virus-derived genetic elements present in host chromosomes. Although these eukaryotic viruses are mostly known to be pathogens, they are also able to establish mutualistic relationships with humans. Little is known about the mutualistic aspects of viral infection. Nevertheless, it is clear that evolution of some animal virus-host interactions has led to benefits in the health of the hosts, as is the case with symbiogenesis and endogenization of retroviruses that has exerted a neuroprotective effect on the human brain, and an important role in the fetal development, thus on the evolution of host species. In this review, we summarize how retroviruses provide amazing examples of cooperative-evolution, i.e., successful exchange between viruses and host, and how, in some cases, the benefits have become essential for the hosts’ survival.